Criterion validity of the Loughborough soccer passing test in elite youth soccer - Serpiello, F. R.; Cox, A.; Oppici, L.; Hopkins, W. G.; Varley, M. C. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
INTRODUCTION: Successful passing is a key component of skilled performance in football, particularly for elite youth players. Owing to the difficulty of assessing passing performance in a controlled environment in games, field tests have been developed to isolate the measurement of this skill. The Loughborough Soccer Passing Test (LSPT) is commonly used to assess passing performance under time pressure. The test is reliable and displays discriminant validity in youth soccer. Here we report its criterion validity with such athletes. METHODS: Twenty-five players from the U18 state representative team (age 15.1 ± 0.6) performed the LSPT. The first eight games of the season were then recorded and coded for passing ability using a custom-made coding window from commercially-available software (Sports-Code, Hudl). Data were coded according to two scenarios. The first reflected overall success rate for all passes within a game. The second scenario represented a high-quality passing situation and passes were included only when they met all the following criteria: the player had performed 3 touches before the pass, the pass lead to a scoring opportunity or forward movement of a team-mate, the pass occurred across halves or in the opponent`s half, and pass direction was forward or sideways. Inter-rater agreement was assessed for overall passing success rate using Cohen`s kappa. Criterion validity of the LSPT scores was assessed as the correlation between the players` mean passing score and their LSPT score. The validity correlation coefficient was then adjusted to take into account the error of the criterion using the intraclass correlation coefficient (ICC) for the mean passing score in 8 games. RESULTS: Inter-rater agreement kappa was 1.00. The ICC for 8-game reliability was 0.67 for overall passing success and 0.75 for the high-quality situation. Overall validity of the LSPT compared to the criterion was very poor for both time-only LSPT (corrected r=0.59) and LSPT total time (corrected r=0.58). Validity of the LSPT compared to the criterion in the high-quality passing scenario was impractical for both time-only LSPT (corrected r=0.32) and LSPT total time (corrected r=0.18). DISCUSSION: This study demonstrated for the first time that the LSPT does not have criterion validity in Australian elite youth football. Despite the strong reliability and discriminant validity, attention must be paid to the interpretation of the test result, as it does not accurately represent in-game passing performance. ABSTRACT FROM AUTHOR